Generalized Aggressive Periodontitis and Its Treatment Options: Case Reports and Review of the Literature - Roshna, T. (Hindawi Publishing Corporation, 2012)
Generalized aggressive periodontitis results in rapid destruction of the periodontium and can lead to early tooth loss in the affected individuals if not diagnosed early and treated appropriately. The diagnostic features of the disease are characteristic, but the clinical presentation and patterns of destructions may vary between patients. Successful management of the disease is challenging especially if diagnosed at advanced stages of the disease, but not impossible with the current therapeutic choices for the disease. A vast array of treatment modalities is available which can be employed in the treatment of generalized aggressive periodontitis with varying success rates, but a definite guideline for the management is yet to be formulated. However, with the exponential rate of developments in periodontal research, regenerative therapy, tissue engineering, and genetic technologies, the future seems promising in regard to options at managing the disease. This paper attempts to describe the clinical and radiographic diagnostic features and the current treatment options along with a suggested protocol for comprehensive management of generalized aggressive periodontitis patients with case reports and a brief review.